Search for direct sbottom and stop pair production in final states with missing transverse momentum and two b-jets with the ATLAS detector - Dafinca, A; Lari, T (2013)
We report on a search for pair production of the scalar partners of bottom and top quarks in 20.1 fb of pp collisions at a centre-of-mass energy of 8 TeV using the ATLAS experiment at the Large Hadron Collider. The study focuses on final states with large missing transverse momentum, no leptons (electrons or muons) and two jets, each identified as originating from a b-quark. This final state can be produced in a R-parity conserving minimal supersymmetric scenario, when the scalar bottom decays into a bottom quark and a neutralino or the scalar top decays into a bottom quark and a chargino, with a small mass difference with the neutralino. © Copyright owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial- ShareAlike Licence.